(untitled) (International Journal of Engineering and Computer Science, 2014)
Fingerprints are the most common and widely accepted biometric feature for person identification and verification in the field of biometric identification. Fingerprints consists of two main types of features : (i) Ridge and Furrow structure: Ridge ends and bifurcation and (ii) Core Point: the of maximum curvature in central region of the fingerprint. This paper presents the implementation of a minutiae based approach to fingerprint identification and verification and serves as a review of the different techniques used in various steps in the development of minutiae based Automatic Fingerprint Identification System (AFIS). The technique conferred in this paper is based on the extraction of ridge termination and virtual core minutiae from the thinned, binarized and segmented version of a fingerprint image.